Fiscal Effects of the Voter Initiative: Evidence from the Last 30 Years - Matsusaka, John G. (Journal of Political Economy, 1995)
In 23 American states, citizens can initiate and approve laws by popular vote; in the other 27 states, laws can be proposed only by elected representatives. This paper compares the fiscal behavior of state and local governments over the last 30 years under these two institutional arrangements. The main finding is that spending is significantly lower, on the order of 4 percent, in states with voter initiatives than in pure representative states. It is also found that local spending is higher and state spending is lower in initiative states. On the revenue side, initiative states rely less on broad-based taxes and more on charges tied to services. Taken together, the evidence indicates that the initiative leads to a reduction in the overall size of the government sector and suggests that it causes a decline in the level of redistributional activity.